Get the answers you've been looking for with the help of IDNLearn.com's expert community. Ask your questions and receive detailed and reliable answers from our experienced and knowledgeable community members.

Evaluate the expression when [tex] x = 4 [/tex] and [tex] y = 7 [/tex].

[tex]\[ 3(3x + y) - 5x + 13 \][/tex]


Sagot :

Certainly! Let's evaluate the expression [tex]\( 3(3x + y) - 5x + 13 \)[/tex] step by step for the given values of [tex]\( x = 4 \)[/tex] and [tex]\( y = 7 \)[/tex].

1. Substitute the given values into the expression:
[tex]\[ x = 4, \quad y = 7 \][/tex]
The expression becomes:
[tex]\[ 3(3(4) + 7) - 5(4) + 13 \][/tex]

2. Simplify inside the parentheses:
First, calculate [tex]\(3(4)\)[/tex]:
[tex]\[ 3(4) = 12 \][/tex]
Then add [tex]\(y\)[/tex] (which is 7) to this product:
[tex]\[ 12 + 7 = 19 \][/tex]

3. Multiply the result by 3:
[tex]\[ 3(19) = 57 \][/tex]

4. Subtract [tex]\(5x\)[/tex] where [tex]\(x = 4\)[/tex]:
Calculate [tex]\(5(4)\)[/tex]:
[tex]\[ 5(4) = 20 \][/tex]
Then subtract this result from 57:
[tex]\[ 57 - 20 = 37 \][/tex]

5. Finally, add 13:
[tex]\[ 37 + 13 = 50 \][/tex]

Therefore, the expression evaluates to:
[tex]\[ 3(3x + y) - 5x + 13 = 50 \][/tex]

So, the answer is:
[tex]\[ 50 \][/tex]